PENGARUH MANAJEMEN WAKTU DAN INTENSITAS KEGIATAN EKSTRAKURIKULER TERHADAP HASIL BELAJAR SISWA SMA - Dwi Cahyati; kuswanto . (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2026)
Several factors affect student learning outcomes, such as the capacity to manage time and the level of involvement in extracurricular activities. Knowing the influence of time management (X1) and the intensity of extracurricular activities (X2) on student learning outcomes (Y) is the purpose of this study. Types of associative research are explored in this study, which uses a quantitative approach. The research sample consisted of 50 students with 20 statement items analyzed using IBM SPSS Statistics 25. The results of the validity test showed a calculated r-value of 0.652–0.815 with a significance of 0.000 < 0.05, while the reliability test obtained a Cronbach's Alpha value of 0.763 > 0.70. Classical assumption test, the data showed a normal distribution, there was no multicollinearity or heteroscedasticity. The t-test results indicated that time management had a significant effect on learning outcomes with a t count of 2.974 (sig. 0.005) and extracurricular activities with a t count of 3.022 (sig. 0.004). The F test obtained a score of 106.951 with a 0.000 significance level and a coefficient of determination (R²) of 0.819.